2020
DOI: 10.1364/ol.389117
|View full text |Cite
|
Sign up to set email alerts
|

Bend-insensitive bismuth-doped P2O5-SiO2 glass core fiber for a compact O-band amplifier

Abstract: For the first time, we report on the fabrication of a bend-insensitive single-mode bismuth (Bi)-doped P 2 O 5 − S i O 2 fiber having a depressed cladding design and study its gain characteristics at a spectral region of 1.3–1.4 µm. It was shown that the obtained Bi-doped fiber can efficiently operate in the spectral band even at a bend radius of 1.5 cm. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The shapes of the gain spectra obtained are similar to the best published results. This result, providing extremely important advantage of compactness, was expected because the effect of the macrobending loss in the active fiber is negligible as it was shown in 17 . In the case of the bi-directional pumping configuration, the gain spectrum is clearly narrower that is explained by the insertion loss due to an additional fused WDM.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…The shapes of the gain spectra obtained are similar to the best published results. This result, providing extremely important advantage of compactness, was expected because the effect of the macrobending loss in the active fiber is negligible as it was shown in 17 . In the case of the bi-directional pumping configuration, the gain spectrum is clearly narrower that is explained by the insertion loss due to an additional fused WDM.…”
Section: Resultsmentioning
confidence: 64%
“…1b. In our previous paper 17 , it was shown that this fiber has an excellent waveguide stability in the spectral region 1300-1400 nm even at a small bending radius of ≈1.5 cm. Thus, this approach can be used to produce a singlemode Bi-doped fiber with a smaller core diameter that is perspective for reducing the saturation power.…”
Section: During Last Decades There Has Been Considerable Interest In mentioning
confidence: 87%
See 2 more Smart Citations
“…Phase and group refractive indices of the fundamental mode in optical fibers are key parameters for accurate design and characterization of optical systems in such fields as telecommunications, laser technology, nonlinear phenomena, metrology or sensors. The two indices can be calculated from measurements of the index profile in the cross section of the fibers [1] or of fiber the preforms [2]. These interferometric or diffractive techniques require special calculation software since actual fibers do not have an exact a step index profile and, what is more, the index profile is measured with reference to a matching index liquid [3,4], which imposes a limit to the accuracy of results.…”
Section: Introductionmentioning
confidence: 99%